Model Kolaboratif Pengusaha Pariwisata dan Pengungsi dalam Konteks Bencana Erupsi Gunung Agung di Desa Wisata Kerta, Kabupaten Gianyar, Bali - Nugroho, Saptono; Arida, I Nyoman Sukma; Ariana, I Nyoman Jamin (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i01.p09, 2021)
This article seeks to find a sustainable model of handling refugees based on the kind of social solidarity that builds between refugees and tourism entrepreneurs amid the disaster. The research took place in Kerta Tourism Village, Gianyar Regency, Bali with the consideration of the unique phenomenon of productive and professional working relationship between the two actors. This fact is seen as able to deconstruct the stereotype of refugees as a group that only needs pity, resulting in a "santa claus" model of assistance. The implementation of research uses a qualitative approach. Qualitative approach to describe and explain phenomena or relationships between phenomena that are systematically reviewed, factual and accurate. The results showed the following findings: (i) economic settings between refugees and entrepreneurs are framed in the context of semi-productive relations; (ii) social settings between refugees and entrepreneurs are built on mechanical solidarity; and (iii) cultural settings between refugees and entrepreneurs are framed in the context of a volatile patron-client relationship, as well as (iv) the discovery of formulations in the form of participatory models of tourism stakeholders in the context of catastrophic eruptions. Keywords: Tourism Entrepreneurs, Refugees, Disaster Eruptions, Collaborative Models